ENGAGING IN INFORMATION ACTIVITIES AND EMPLOYING INTERACTIVE LEARNİNG TECHNIQUES - Nodir Jamalov (American Journals Publishing, 2023)
The article focuses on interactive learning methodologies, highlighting the acquisition of knowledge and the development of skills and abilities within the context of teacher-student interactions in educational settings. Central to these methods is their emphasis on not only cognitive processes like perception, memory, and attention but, more importantly, on nurturing creative, productive thinking, behavior, and effective communication. This instructional approach is structured to enable students to enhance their communication and interaction skills both among their peers and with external individuals. It also fosters critical thinking and problem-solving, utilizing the analysis of workplace scenarios, situational professional tasks, and relevant information as key components of the learning process.
Keywords: Interactive Learning Approaches, Acquisition of Knowledge, Skill Development, Competency Building, Educational Focus, and Analyzing Interaction.